HIDUP SEBAGAI ORANG-ORANG ARIF SUATU TAFSIRAN TERHADAP EFESUS 5:15 - 21 - Tony Suhartono; Andre Djaafar; Suhendra Suhendra (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
In the era of digital 4.0, where technology advances rapidly, many people seek to do everything quickly. This phenomenon also affects Christians, who aspire to embody the teachings of the Bible, but often wish to skip the process of growth and transformation. However, it is through the experiences and events of life that individuals are meant to undergo character development, becoming wise individuals rather than the opposite, becoming